2022
DOI: 10.1038/s41419-022-04793-x
|View full text |Cite
|
Sign up to set email alerts
|

MFSD4A inhibits the malignant progression of nasopharyngeal carcinoma by targeting EPHA2

Abstract: DNA Methylation can lead to abnormal gene expression. In the present study, we investigated whether the expression of methylated MFSD4A (major facilitator superfamily domain containing 4 A) was downregulated in nasopharyngeal carcinoma (NPC) and whether it is associated with malignant progression and poor prognosis of NPC. Bioinformatic analysis, bisulfite pyrosequencing, quantitative real-time reverse transcription PCR, and western blotting assays were performed to explore the relationship between hypermethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…However, reports regarding its functions in cells are few. It has been reported that RNF149 promotes cell survival in colorectal cancer [10] and inhibits cell migration in NPC [11]. Additionally, RNF149 is found to involve the development of rat neonatal gonocytes [29].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, reports regarding its functions in cells are few. It has been reported that RNF149 promotes cell survival in colorectal cancer [10] and inhibits cell migration in NPC [11]. Additionally, RNF149 is found to involve the development of rat neonatal gonocytes [29].…”
Section: Discussionmentioning
confidence: 98%
“…As an E3 ubiquitin ligase, only two experimentally validated substrates of RNF149 were reported so far: wild-type but not mutant BRAF in colorectal cancer [10], and EPHA2 in NPC [11]. To discover the substrate of RNF149 in HCC, we focused on the proteins which both showed significant downregulation in RNF149-overexpressed HCC cells and interacted with RNF149, and DNAJC25 was the only candidate with high confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM50 encodes an E3 ubiquitin-protein ligase that ubiquitinates Beclin-1/BECN1 to promote autophagy activation, and its RNA expression is enriched in liver and renal cancer [ 26 , 27 ]. In addition, Yang et al [ 28 ] demonstrated that MFSD4A could specifically bind to and degrade EPH receptor A2 (EPHA2), leading to alterations in the PI3K-AKT-ERK1/2 pathway and epithelial-mesenchymal transition, thereby affecting nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Through GO enrichment analysis, KEGG pathway enrichment analysis, and literature review, we focused on EPHA2, a protein related to the PI3K/ Akt pathway that affects macrophage polarization after LDHA knockdown (Figure 5C,D). 27,28 F I G U R E 4 (See caption on next page).…”
Section: Ldha Overexpression In Ccrcc Was Correlated With Macrophage ...mentioning
confidence: 99%